Exploring Brand Gestalt Dimensions in the Tomohon International Flower Festival - Patricia Gabriela Rawung; Jane Dungus; Deske W. Mandagi (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Understanding the dimensions that shape a festival’s brand gestalt is crucial for enhancing its appeal and long-term success. This study aims to examine the influence of storyscape, sensescape, servicescape, and stakeholder engagement on brand gestalt in the context of the Tomohon International Flower Festival. A quantitative research approach was employed using Structural Equation Modeling to analyze the relationships among these variables. Data were collected from 171 respondents, consisting of festival attendees, through an online survey. The hypothesis testing results indicate that sensescape and stakeholder engagement have a significant positive effect on brand gestalt, while storyscape and servicescape do not exhibit a significant influence. These findings suggest that sensory experiences and stakeholder involvement are key drivers in shaping the festival’s brand gestalt, whereas narrative elements and physical servicescape aspects may play a less critical role. The study offers theoretical contributions by expanding the understanding of festival branding through the brand gestalt framework and provides practical implications for event organizers in designing impactful festival experiences.